2018
DOI: 10.1523/jneurosci.0705-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

A Central Extended Amygdala Circuit That Modulates Anxiety

Abstract: Both the amygdala and the bed nucleus of the stria terminalis (BNST) have been implicated in maladaptive anxiety characteristics of anxiety disorders. However, the underlying circuit and cellular mechanisms have remained elusive. Here we show that mice with gene deficiency in somatostatin-expressing (SOM) neurons exhibit heightened anxiety as measured in the elevated plus maze test and the open field test, two assays commonly used to assess anxiety-related behaviors in rodents. Using a combination of electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 84 publications
7
120
2
Order By: Relevance
“…A recent study showed that local photoactivation of all Som BNST neurons drives anxietymediated avoidance in the EPM (Ahrens et al, 2018). Therefore, investigating the role of how Pnoc + /Som + and Pnoc + /Somneurons might differ in the regulation of anxiety-like behavior and arousal responses deserves further attention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that local photoactivation of all Som BNST neurons drives anxietymediated avoidance in the EPM (Ahrens et al, 2018). Therefore, investigating the role of how Pnoc + /Som + and Pnoc + /Somneurons might differ in the regulation of anxiety-like behavior and arousal responses deserves further attention.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their interconnectedness and similarity, research indicates that the BNST and the amygdala nuclei work in accordance to mediate a variety of behaviors, in particular anxiety‐ and fear‐related behaviors (Davis et al, ). For example, projections from the CM to the BNST can increase measures of anxiety in mice (Ahrens et al, ) and precise optogenetic stimulation of LB terminals in the CM induces anxiolytic effects, whereas inhibition results in an increase in anxiety‐related behaviors in mice (Tye et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The CeL modulates the CeM, helping to orchestrate the different adaptive behavioral and physiological responses mediated by the CeM's targets (Haubensak et al, 2010;Viviani et al, 2011). The entire Ce projects to the BST to further coordinate threat-related responding, where the CeL's projections are largely restricted to laterodorsal BST (BSTLd), (Ahrens et al, 2018;Asok et al, 2018;Oler et al, 2017;Pomrenze et al, 2019). In addition to other areas of the basal forebrain, the CeL, CeM, and the BSTLd have been conceptualized as the central extended amygdala, in contrast to what is considered the medial extended amygdala which is comprised of the medial nucleus of the amygdala and the medial divisions of the BST (Alheid and Heimer, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on the primate CeL because studies in rodents demonstrate that it integrates information from the basolateral amygdala complex and acts as an interface between the basolateral amygdala complex and the CeM and BSTLd (Dong et al, 2001;LeDoux et al, 1990;Petrovich and Swanson, 1997;Yu et al, 2017). Studies demonstrate that within the CeL, GABAergic neuronal subtypes interact to affect CeM and BSTLd function (Ahrens et al, 2018;Asok et al, 2018;Haubensak et al, 2010;Petrovich and Swanson, 1997;Pomrenze et al, 2019). For example, protein kinase C type delta (gene name: PRKCD, protein name: PKCd) and somatostatin (gene name: SST, protein name: SST) expressing neurons are two prominent cell types that are involved in a mutually inhibitory CeL microcircuit, integrating and gating the flow of threat-related information to the CeM and BSTLd (Fadok et al, 2018;Haubensak et al, 2010;Li et al, 2013;Ye and Veinante, 2019).…”
Section: Introductionmentioning
confidence: 99%